An Old Mind in a New “Body” by Hanif Kureishi - Ayşe Demir (Literacy Trek, 2019)
Finding ways to live an eternal life has always been an issue that intrigues the minds of people and finds an important place in literary works, as well. At times, the key to live forever is through a magical touch; sometimes it is a scientific experiment on dead ones and it might also be a surgical operation that helps the characters sustain an endless life just like Hanif Kureishi’s novella, “The Body” in which Kureishi introduces the reader an old, famous playwright named Adam who is offered a chance to live a second life in a different body. The novella is mainly based on the operation that transplant Adam’s brain into a brand new body. Everything seems perfect at the beginning; he experiences an almost hedonistic lifestyle, but the accumulated experiences of his past life do not leave him. In other words, his consciousness, thoughts and memories are also transferred into his new body creating a big dilemma for Adam. The paradox he experiences, caused by an old mind in a new body, evokes the present subject of this paper; namely the dual nature of flesh and spirit, body and mind. Therefore, this paper aims to explore these dualities together with their effects on the individual and social self.